The Implementation of Convolutional Neural Network in Recognize Lontara Text - Arthanugraha, Wahyu; Zainuddin, Zahir; Arda, Abdul Latief (Jurnal Informatika, 2024)
The introduction of the Lontara text that is applied is still conventional in that it comes from books or teaching materials and there is no application for a translator of the Lontara text, making it difficult for students, especially those from outside the Bugis tribe. This research aims to measure the ability and apply the CNN method in the context of introducing the Lontara text. The input that use in this research is words taken from the original text or writing manuscripts of the ancient literature of the Bugis tribe "Sureq Maqkelluqna Nabittaq", a book that was used as a tool to spread Islam in 1611. The model used is the VGG-16 architecture. This research uses the R&D (Research and Development) method which is used to create products and test their level of effectiveness. As for the research results obtained, the system accuracy obtained in classifying the Lontara text using the VGG16 architecture was 97,65%. In addition, the system is also able to display the translation of the Lontara text according to the database input.